Carbon-based materials for three-dimensional electrode filling, methods of making and using the same

By preparing carbon-based materials filled with three-dimensional electrodes, the low utilization rate and industrialization problems of oily sludge residue treatment were solved, achieving high-efficiency catalytic performance and resource utilization, thus achieving both environmental and economic benefits.

CN116920897BActive Publication Date: 2025-12-12CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210323939.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-29
Publication Date
2025-12-12
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

The utilization rate of residue after oily sludge treatment in existing technologies is not high, pyrolysis residue treatment technology is difficult to achieve industrial application, and there are few reports on residue treatment technologies after other treatment methods, which pose environmental hazards and resource waste problems.

Method used

A carbon-based material for filling three-dimensional electrodes was prepared by pyrolyzing waste biomass and oily sludge residue in the presence of an activator. This material was then applied in a three-dimensional electrolysis reactor as a filler between the cathode and anode, and was combined with a binder for molding and drying.

Benefits of technology

This study achieved highly efficient catalytic performance of three-dimensional electrode filling materials, reduced production costs, and enabled the resource utilization of waste, resulting in significant economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003571044240000091
    Figure BDA0003571044240000091
  • Figure BDA0003571044240000092
    Figure BDA0003571044240000092
  • Figure BDA0003571044240000101
    Figure BDA0003571044240000101
Patent Text Reader

Abstract

The application relates to the field of electro-catalytic oxidation degradation, and discloses a carbon-based material for three-dimensional electrode filling and a preparation method and application thereof.The carbon-based material contains C, H, O, N, S, Fe, Si and Mn.The carbon-based material for three-dimensional electrode filling has the advantages of stable performance, high catalytic efficiency and low price; can realize the purpose of changing waste into treasure and treating waste with waste; can achieve the dual purposes of solid waste resource utilization and pollutant removal; and has good economic, environmental and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of electro-catalytic oxidation degradation, in particular, to a carbon-based material for three-dimensional electrode filling and a preparation method and application thereof. BACKGROUND

[0002] Three-dimensional electrode technology is to fill a granular electrode as a third electrode between the two electrode plates of the traditional two-dimensional plate electrode. Granular, sheet or powder materials, etc. can be generally used as the granular electrode in the three-dimensional electrode system, which is located between the anode and the cathode without direct resistance contact with the electrode, thereby enhancing the distribution of ion charge. Under the condition of external voltage on the plate electrode, the granular will be polarized to form a micro polarized electrode under the action of the electric field.

[0003] Compared with the two-dimensional electrolytic tank, the specific surface area of the three-dimensional electrode is increased, the effective treatment amount of the pollutant is increased, and the particle spacing is small, so that the mass transfer effect of the substance is greatly improved, and the effective current utilization rate is improved.

[0004] The petroleum chemical industry will produce a large amount of oily sludge, which has great environmental hazards, and the scientific and reasonable disposal problem is a difficult problem to be solved in the environmental field.

[0005] At present, many countries have classified the residue after the treatment of oily sludge as hazardous waste, and the residue after the treatment still retains the hazardous characteristics of oily sludge, and the lower the treatment efficiency, the greater the toxicity and pollution.

[0006] The residue after the treatment of oily sludge contains incompletely recovered oil resources and residual heavy metals and other harmful substances, and if the destination cannot be effectively solved, it will restrict the development of oily sludge treatment technology, so the treatment research of oily sludge residue has practical significance.

[0007] CN111167408A discloses a method for preparing an adsorbent material from oil sludge residue, which comprises soaking the oil sludge residue obtained by pyrolysis of oil sludge in an ammonium salt solution for a certain time, then filtering, and placing the filter cake in a tube furnace under nitrogen protection, rapidly heating to 450-650℃, and carbonizing at constant temperature for 1-6h to obtain carbon adsorbent material.

[0008] CN112047436A discloses a method for preparing a micro-electrolysis filler from oil sludge pyrolysis residue, which comprises crushing the oil sludge pyrolysis residue, uniformly mixing with reduced iron powder and high clay, adding water, and forming into a ball with a briquette machine, and sintering in a 300-600℃ sintering furnace for 1-4h to obtain a micro-electrolysis filler.

[0009] CN102294217A discloses a method for preparing a new oil extraction wastewater adsorbent by using oil sludge pyrolysis residues, which comprises grinding and screening the oil sludge pyrolysis residues, acid impregnation treatment, rinsing to neutral, mixing with polytetrafluoroethylene, cold pressing, carbonization, rinsing and drying to prepare the oil extraction wastewater adsorbent.

[0010] CN113149493A discloses a method for preparing artificial light aggregate by using oil sludge pyrolysis residues, which comprises mixing the oil sludge pyrolysis residues and rice chaff, balling in a disc balling machine to obtain pellets, and performing natural drying curing and high-temperature calcination to obtain the artificial light aggregate product.

[0011] At present, there are not many studies on how to treat the residue after the treatment of oil-containing sludge, and the above-mentioned prior art is mostly focused on the treatment of solid residues generated after the pyrolysis of oil-containing sludge, and there are few reports on the treatment technology of residues treated by extraction, hot washing and other methods.

[0012] In addition, there are problems such as low utilization rate of oil-containing sludge pyrolysis residues, low content of pyrolysis residues and difficulty in industrial application of the technology. SUMMARY

[0013] The purpose of the present application is to overcome the aforementioned problems existing in the prior art, and to provide a three-dimensional electrode filling material by utilizing waste biomass and oil-containing sludge residues and combining the characteristics of the three-dimensional electrode filling material.

[0014] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a carbon-based material for three-dimensional electrode filling, which contains C with a mass percentage of 18.06-25.50%, H with a mass percentage of 1.36-1.67%, O with a mass percentage of 10.57-13.57%, N with a mass percentage of 0.19-0.72%, S with a mass percentage of 4.11-6.10%, Fe with a mass percentage of 26.20-32.20%, Si with a mass percentage of 2.08-3.40%, and Mn with a mass percentage of 0.27-0.36%.

[0015] The second aspect of the present application provides a method for preparing a carbon-based material for three-dimensional electrode filling, which comprises:

[0016] In a protective atmosphere, the solid residue is contacted with the waste biomass in the presence of an activating agent to perform pyrolysis, to obtain a mixture I;

[0017] The mixture I is contacted with a binder to perform molding and drying;

[0018] The solid residue contains, by mass percentage, 20.06-30.27% C, 2.38-4.73% H, 15.80-18.50% O, 0.33-0.56% N, 3.25-6.68% S, 22.58-34.40% Fe, 2.45-4.13% Si, and 0.29-0.56% Mn.

[0019] A third aspect of the present invention provides a carbon-based material for filling three-dimensional electrodes, prepared by the method described in the second aspect above.

[0020] A fourth aspect of the present invention provides the application of the carbon-based material for filling three-dimensional electrodes as described in the first or third aspect above in the electrocatalytic oxidation degradation of organic wastewater.

[0021] A fifth aspect of the present invention provides a three-dimensional electrolysis reactor, wherein the filling material between the cathode and the anode of the reactor is a carbon-based material for filling three-dimensional electrodes as described in the first or third aspect above.

[0022] The present invention has at least the following advantages:

[0023] (1) The carbon-based material for filling three-dimensional electrodes provided by the present invention has the advantages of stable performance, high catalytic efficiency and low price.

[0024] (2) The method for preparing carbon-based materials for filling three-dimensional electrodes provided by the present invention has the advantages of simple process, convenient operation and low production cost.

[0025] (3) The present invention uses the residue of oily sludge generated in the petrochemical field to prepare carbon-based materials for filling three-dimensional electrodes, which can realize the purpose of turning waste into treasure and treating waste with waste, and achieve the dual purpose of solid waste resource utilization and pollutant removal, and has good economic, environmental and social benefits. Detailed Implementation

[0026] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0027] As described above, the first aspect of the present application provides a carbon-based material for three-dimensional electrode filling, wherein the carbon-based material contains C in a mass percentage of 18.06-25.50%, H in a mass percentage of 1.36-1.67%, O in a mass percentage of 10.57-13.57%, N in a mass percentage of 0.19-0.72%, S in a mass percentage of 4.11-6.10%, Fe in a mass percentage of 26.20-32.20%, Si in a mass percentage of 2.08-3.40%, and Mn in a mass percentage of 0.27-0.36%.

[0028] Preferably, the carbon-based material contains C in a mass percentage of 18.06-24.91%, H in a mass percentage of 1.36-1.50%, O in a mass percentage of 10.57-13.57%, N in a mass percentage of 0.19-0.72%, S in a mass percentage of 4.11-6.10%, Fe in a mass percentage of 26.20-32.20%, Si in a mass percentage of 2.08-3.40%, and Mn in a mass percentage of 0.29-0.36%.

[0029] Preferably, the specific surface area of the carbon-based material is 244-409 m 2 / g, the mesopore area is 145-189 m 2 / g, and the micropore area is 98-220 m 2 / g. The inventors of the present application have found that when the mesopore area of the carbon-based material is 153-189 m 2 / g, the carbon-based material has higher catalytic efficiency when used for electrocatalytic oxidation of organic wastewater.

[0030] As described above, the second aspect of the present application provides a method for preparing a carbon-based material for three-dimensional electrode filling, the method comprising:

[0031] contacting the solid residue with the waste biomass under a protective atmosphere in the presence of an activating agent to perform pyrolysis, to obtain a mixture I;

[0032] contacting the mixture I with a binder to perform molding and drying;

[0033] The solid residue contains C with a mass percentage of 20.06-30.27%, H with a mass percentage of 2.38-4.73%, O with a mass percentage of 15.80-18.50%, N with a mass percentage of 0.33-0.56%, S with a mass percentage of 3.25-6.68%, Fe with a mass percentage of 22.58-34.40%, Si with a mass percentage of 2.45-4.13%, and Mn with a mass percentage of 0.29-0.56%. In the present application, in order to make the solid residue and the waste biomass better pyrolyzed, the solid residue and the waste biomass are preferably crushed before the pyrolysis to obtain powders with an average particle size of 300-850 μm.

[0034] Preferably, the solid residue is selected from at least one of a solid residue after oil sludge treatment, a solid residue after municipal sludge dewatering, a solid residue after refinery oil sludge dewatering, a solid residue after refinery scum dewatering, and a solid residue after refinery activated sludge dewatering.

[0035] Preferably, the waste biomass is selected from at least one of wheat straw, rice straw, corn straw, dried fruit shells, tree leaves, straw, and wood chips.

[0036] Preferably, the waste biomass has a water content of <10 wt%.

[0037] Preferably, the solid residue and the waste biomass are used in a weight ratio of 1:0.2-1.0.

[0038] Preferably, the total amount of the solid residue and the waste biomass is 1 g, and the amount of the activator is 0.3-1.0 g.

[0039] Preferably, the mixture I and the binder are used in a weight ratio of 1:0.1-0.5.

[0040] Preferably, the activator is selected from at least one of phosphoric acid, zinc chloride, potassium hydroxide, and sodium carbonate.

[0041] Preferably, the binder is selected from at least one of sodium alginate, phenolic resin, polyvinyl alcohol, and chitosan.

[0042] More preferably, the binder is sodium alginate. The inventors of the present application have found that, in this preferred case, the carbon-based material prepared for three-dimensional electrode filling has higher catalytic efficiency when used for electrocatalytic oxidation of organic wastewater.

[0043] According to a preferred embodiment, the pyrolysis is performed under conditions that at least meet the following requirements: the initial temperature is 20-40℃, the final temperature is 400-800℃, the temperature rising rate is 5-20℃ / min, and the constant temperature time at the final temperature is 1-3h.

[0044] According to another preferred embodiment, the flow rate of the protective atmosphere is 200-600mL / min.

[0045] It should be noted that the present application does not have any particular limitation on the forming method, and those skilled in the art can select according to the technical means known in the art. A preferred embodiment is exemplarily provided in the following of the present application, and those skilled in the art should not understand it as a limitation on the present application.

[0046] It should be noted that the protective atmosphere in the present application refers to an inert gas atmosphere. Exemplarily, the protective atmosphere can be nitrogen or argon.

[0047] Preferably, the drying is performed under conditions that at least meet the following requirements: the drying temperature is 80-110℃, and the drying time is 2-6h.

[0048] Further preferably, the drying is performed under conditions that at least meet the following requirements: the drying temperature is 90-105℃, and the drying time is 2-4h.

[0049] It should be noted that the present application does not have any particular limitation on the drying method, and various drying methods known in the art can be used. Exemplarily, the drying method can be oven drying, freeze drying, supercritical drying, or spray drying.

[0050] As described above, the third aspect of the present application provides a carbon-based material for three-dimensional electrode filling, which is prepared by the method of the aforementioned second aspect.

[0051] As described above, the fourth aspect of the present application provides an application of the carbon-based material for three-dimensional electrode filling of the aforementioned first aspect or third aspect in electrocatalytic oxidation degradation of organic wastewater.

[0052] As described above, the fifth aspect of the present application provides a three-dimensional electrolysis reactor, in which the filling material between the cathode and the anode is the carbon-based material for three-dimensional electrode filling of the aforementioned first aspect or third aspect.

[0053] Preferably, the filling material is a cylinder, a cuboid, a cube, or a sphere.

[0054] More preferably, the filling material is a cylinder. The inventors of the present application have found that in this preferred case, the three-dimensional electrolysis reactor has higher catalytic efficiency when used for electrocatalytic oxidation of organic wastewater.

[0055] It should be noted that the present application does not have a particular limitation on the material type of the cathode and the anode in the three-dimensional electrolysis reactor, and those skilled in the art can select in combination with the known technical means in the art. Exemplarily, the cathode material can be graphite, graphite felt, carbon felt, stainless steel plate, etc., and the anode material can be titanium iridium ruthenium, titanium ruthenium, metal oxide, etc. Those skilled in the art should not be construed as a limitation on the present application.

[0056] It should be noted that the present application does not have a particular limitation on the specific structure of the three-dimensional electrolysis reactor, and those skilled in the art can select in combination with the known technical means in the art. Exemplarily, a preferred specific manner is provided in the following of the present application, and those skilled in the art should not be construed as a limitation on the present application.

[0057] Preferably, the specific structure of the three-dimensional electrolysis reactor is as follows:

[0058] The geometric size of the electrolysis reactor is 15 cm x 9.3 cm x 20 cm (length x width x height), the anode of the electrolysis reactor is a titanium ruthenium iridium mesh electrode, the cathode is a graphite electrode, and the anode and the cathode contain a filler material; the walls at both ends of the electrolysis reactor are provided with a grid to adjust the distance between the electrodes; the bottom of the electrolysis reactor is provided with an aeration hole and a sand core, and the sand core serves to make the gas passed more uniform, reduce the volume of the gas bubbles, and ensure that the filler material is uniformly suspended in the electrolysis reactor.

[0059] The present application will be described in detail by examples as follows. In the following examples, the room temperature means 25±5℃ unless otherwise specified.

[0060] Preparation Example 1: Preparation of carbon-based material C1

[0061] Under the protection of nitrogen gas with a flow rate of 200 mL / min, 30 g of solid residue (average particle size of 300 μm, source: oil-containing sludge taken from Jingmen petrochemical refinery, oil-containing solid residue obtained after extraction), 15 g of waste biomass (wheat straw, average particle size of 300 μm, water content of 8.7 wt%), and 15 g of activating agent (potassium hydroxide) were mixed and placed in a quartz tube furnace, and then heated at a rate of 10℃ / min from room temperature to 700℃, and then kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain the mixture I;

[0062] 50 g of the mixture I and 5 g of the binder (sodium alginate) were extruded into a cylindrical shape with a diameter of 5 mm and a length of 1 cm by an extruder (Guangzhou Huagong Machinery and Electrical Technology Co., Ltd., Model: F-26 double screw extruder), and then dried at 105℃ for 2 h to obtain the carbon-based material C1.

[0063] Preparation Example 2: Preparation of carbon-based material C2

[0064] The present preparation example was carried out using a similar process to Preparation Example 1, except that in the present preparation example:

[0065] The preparation formula and process parameters for the carbon-based material used were different, and are specifically shown in Table 2.

[0066] The carbon-based material C2 was prepared.

[0067] Preparation Example 3

[0068] The present preparation example used a similar formula and method to Preparation Example 1 to prepare the carbon-based material, except that the sodium alginate in Preparation Example 1 was replaced with an equal weight of chitosan, and the carbon-based material C3 was prepared, as shown in Table 2.

[0069] Preparation Example 4

[0070] The present preparation example used a similar formula and method to Preparation Example 1 to prepare the carbon-based material, except that extrusion molding was used to obtain a cuboid-shaped carbon-based material C4 with dimensions of 1 cm x 5 mm x 5 mm, as shown in Table 2.

[0071] Preparation Example 5

[0072] The present preparation example used a similar formula and method to Preparation Example 1 to prepare the carbon-based material, except that the amount of activator in Preparation Example 1 was 11 g, and the carbon-based material C5 was prepared, as shown in Table 2.

[0073] Note: The same solid residue was used in the above preparation examples, and the chemical composition of the solid residue is shown in Table 1.

[0074] Comparative Example 1

[0075] The present preparation example used a similar formula and method to Preparation Example 1 to prepare the carbon-based material, except that the solid residue in Preparation Example 1 was replaced with an equal weight of sludge, and the carbon-based material DC1 was prepared, as shown in Table 2.

[0076] Note: The sludge in the present comparative example was obtained from the sludge treatment site of Jingmen Petrochemical, and the chemical composition of the sludge is shown in Table 1.

[0077] Test Example

[0078] The carbon-based material prepared in the preparation example was used as the filling material of a three-dimensional electrolysis reactor, and electrolysis test was performed on the material to be electrolyzed, the anode of the three-dimensional electrolysis reactor was a titanium-ruthenium-iridium plate (purchased from Xinxiang Future Water Chemical Co., Ltd.), the cathode was graphite (purchased from Beijing Jinglongte Carbon Technology Co., Ltd.), the distance between the anode and the cathode was 4 cm, and the carbon-based material prepared in the preparation example, cylindrical activated carbon I (purchased from Xinghua Carbon Technology Co., Ltd.) and cylindrical activated carbon II (purchased from Jiangsu Enkai Activated Carbon Co., Ltd.) were used as the third electrode; the electrolysis pressure was 12 V, the concentration of the electrolysis objects aniline and methyl orange was 200 mg / L, and the test results are shown in Table 5.

[0079] Table 1

[0080]

[0081] Table 2

[0082]

[0083]

[0084] Table 3: Chemical composition of the carbon-based material prepared in each preparation example and comparative example

[0085] C H O N S Fe Si Mn Preparation Example 1 24.91 1.50 12.02 0.60 4.32 26.80 2.26 0.29 Preparation Example 2 18.06 1.42 13.41 0.72 4.11 32.20 2.08 0.36 Preparation Example 3 23.72 1.36 13.57 0.52 4.89 26.20 3.40 0.35 Preparation Example 4 24.89 1.48 12.00 0.58 4.33 26.90 2.27 0.30 Preparation Example 5 25.50 1.67 13.05 0.54 4.12 27.40 2.12 0.27 Comparative Example 1 15.64 0.14 18.70 6.95 5.45 4.64 22.45 1.45

[0086] Table 4: Characteristic parameters of the carbon-based material prepared in each preparation example and comparative example

[0087] Specific surface area (m 2 / g) Mesopore area (m 2 / g) micropore area (m 2 / g) Preparation Example 1 252 151 101 Preparation Example 2 276 169 107 Preparation Example 3 249 149 100 Preparation Example 4 245 146 99 Preparation Example 5 212 109 102 Comparative Example 1 Comparative Example 2 6.59 2.48 4.11

[0088] Table 5

[0089]

[0090]

[0091] As can be seen from the results in Table 5, compared with the existing three-dimensional electrode filling material, the carbon-based material for three-dimensional electrode filling provided by the present application has obviously higher catalytic efficiency when electrolyzing aniline and methyl orange.

[0092] The above describes the preferred embodiments of the present application in detail, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be considered as disclosed by the present application and fall within the protection scope of the present application.

Claims

1. A carbon-based material for three-dimensional electrode filling, characterized by, The carbon-based material contains C with a mass percentage of 18.06-24.91%, H with a mass percentage of 1.36-1.50%, O with a mass percentage of 10.57-13.57%, N with a mass percentage of 0.19-0.72%, S with a mass percentage of 4.11-6.10%, Fe with a mass percentage of 26.20-32.20%, Si with a mass percentage of 2.08-3.40%, and Mn with a mass percentage of 0.29-0.36%; The carbon-based material has a specific surface area of 244-409 m 2 / g, a mesopore area of 145-189 m 2 / g, and a micropore area of 98-220 m 2 / g.

2. A method of making the carbon-based material for three-dimensional electrode filling of claim 1, characterized by, The method comprises: under a protective atmosphere, contacting the solid residue with waste biomass in the presence of an activating agent to perform pyrolysis, to obtain a mixture I; the amount of the activating agent is 0.3-1.0 g, based on 1 g of the total amount of the solid residue and the waste biomass; contacting the mixture I with a binder to perform molding and drying; The solid residue contains C with a mass percentage of 20.06-30.27%, H with a mass percentage of 2.38-4.73%, O with a mass percentage of 15.80-18.50%, N with a mass percentage of 0.33-0.56%, S with a mass percentage of 3.25-6.68%, Fe with a mass percentage of 22.58-34.40%, Si with a mass percentage of 2.45-4.13%, and Mn with a mass percentage of 0.29-0.56%.

3. The method of claim 2, wherein, The weight ratio of the amount of the solid residue to the amount of the waste biomass is 1:0.2-1.

0.

4. The method of claim 2 or 3, wherein, The solid residue is selected from at least one of a solid residue after treatment of oil-containing sludge, a solid residue after dewatering of municipal sludge, a solid residue after dewatering of refinery sludge, a solid residue after dewatering of refinery scum, and a solid residue after dewatering of refinery activated sludge.

5. The method of claim 2 or 3, wherein, The waste biomass is selected from at least one of wheat straw, rice straw, corn straw, dried fruit shells, tree leaves, straw, and wood chips.

6. The method of claim 2 or 3, wherein, The weight ratio of the amount of the mixture I to the amount of the binder is 1:0.1-0.

5.

7. The method of claim 2 or 3, wherein, The activating agent is selected from at least one of phosphoric acid, zinc chloride, potassium hydroxide, and sodium carbonate.

8. The method of claim 2 or 3, wherein, The binder is selected from at least one of sodium alginate, phenolic resin, polyvinyl alcohol, and chitosan.

9. The method of claim 8, wherein, The binder is sodium alginate.

10. The method of claim 2 or 3, wherein, The pyrolysis satisfies at least the following conditions: a starting temperature of 20-40°C, a final temperature of 400-800°C, a temperature rising rate of 5-20°C / min, and a constant temperature time at the final temperature of 1-3 h.

11. The method of claim 2 or 3, wherein, The flow rate of the protective atmosphere is 200-600 mL / min.

12. The method of claim 2 or 3, wherein, The drying satisfies at least the following conditions: a drying temperature of 80-110°C, and a drying time of 2-6 h.

13. A carbon-based material for three-dimensional electrode filling, which is prepared by the method of any one of claims 2-12.

14. Use of the carbon-based material for three-dimensional electrode filling of claim 1 or 13 in electrocatalytic oxidation degradation of organic wastewater.

15. A three-dimensional electrolytic reactor, characterized by The filling material between the cathode and the anode of the reactor is the carbon-based material for three-dimensional electrode filling of claim 1 or 13.

16. The three-dimensional electrolytic reactor of claim 15, wherein, The shape of the filling material is a cylinder, a cuboid, or a sphere.

17. The three-dimensional electrolytic reactor of claim 16, wherein, The shape of the filling material is a cube.

Citation Information

Patent Citations

  • Method for preparing novel oilfield wastewater adsorbents using oil sludge pyrolysis residue

    CN102294217A

  • Method for preparing adsorbing material from oil sludge residues and application thereof

    CN111167408A

  • Method for preparing micro-electrolysis filler from oil sludge pyrolysis residues and application thereof

    CN112047436A

  • Method for preparing artificial lightweight aggregate from oil sludge pyrolysis residues

    CN113149493A

  • Method for preparing particle catalytic electrodes by utilization of sludge and flyash and application of particle catalytic electrodes

    CN106064962A